A phenomenological description of the pressure sensitivity of the Curie temperature in hole-doped manganites - Garbarino, Gaston Leonel (2009)
We performed high-pressure experiments in La0.8Ca0.2-xSr xMnO3 (LCSMO)(0≤ x ≤ 0.2) ceramic samples in order to analyze the validity of the well-known relation between the A-cation mean ionic radius ((ra)) and the Curie temperature Tc of hole-doped manganites at a fixed doping level and for doping values below the 0.3 (Mn+4/Mn+3) ratio. By considering our results and collecting others from the literature, we were able to propose a phenomenological relation that considers the systematic dependence of T c with structural and electronic parameters. The proposed expression predicts fairly well the pressure sensitivity of Tc, its dependence with the A-cation radius disorder and its evolution in the high-pressure range. Considering a Double-Exchange model, modified by polaronic effects, the phenomenological law obtained for Tc can be associated with the product of two terms: the polaronic modified bandwidth and an effective hole doping. Copyright © EPLA, 2009.